Ceftriaxone Ameliorates Motor Deficits and Protects Dopaminergic Neurons in 6-Hydroxydopamine-Lesioned Rats - Leung, T. C. H. (American Chemical Society, 2011)
[Image: see text] Parkinson’s disease is caused by the degeneration of dopaminergic neurons in substantia nigra. There is no current promising treatment for neuroprotection of dopaminergic neurons. Ceftriaxone is a beta-lactam antibiotic and has been reported to offer neuroprotective effects (Rothstein, J.-D., Patel, S., Regan, M.-R., Haenggeli, C., Huang, Y.-H., Bergles, D.-E., Jin, L., Dykes, H.-M., Vidensky, S., Chung, D.-S., Toan, S.-V., Bruijn, L.-I., Su, Z.-Z., Gupta, P., and Fisher, P.-B. (2005) Beta-lactam antibiotics offer neuroprotection by increasing glutamate transporter expression Nature433, 73–77). In the present study, efficacy of ceftriaxone in neuroprotection of dopaminergic neurons and amelioration of motor deficits in a rat model of Parkinson’s disease were investigated. Ceftriaxone was administrated in 6-hydroxydopamine-lesioned rats. Using behavioral tests, grip strength and numbers of apomorphine-induced contralateral rotation were declined in the ceftriaxone-treated group. More importantly, cell death of dopaminergic neurons was found to decrease. In addition, both the protein expression and immunoreactivity for GLT-1 were up-regulated. The present results strongly indicate that ceftriaxone is a potential agent in the treatment of Parkinson’s disease.